Inquiry based experiments to enhance sustainability literacy: A systematic literature review and bibliometric analysis - Shidiq, Ari Syahidul; Huda, Zamira Zia'ul; Yamtinah, Sri; Ulfa, Maria; Masykuri, Mohammad; Saputro, Agung Nugroho Catur (Journal of Environment and Sustainability Education, 2025)
This study aims to explore inquiry-based experiments' educational aspects, levels of inquiry, and contributions to sustainability literacy. In this study, a systematic literature review and bibliometric analysis were used. A systematic literature review in this study used a PRISMA flow diagram, and the bibliometric analysis was conducted using VOS Viewer. Using systematic literature review 79 articles were analyzed, focusing on three main aspects: pedagogy/education, levels of inquiry, and sustainability literacy. A bibliometric analysis was also used in this study.  A RIS format of articles was compiled and then used for the bibliometric analysis using VOSviewer. The bibliometric analysis focused on network overlay, density visualization, and author and co-author relationships. The results of this study indicate that inquiry-based experiments significantly enhance students' understanding of scientific concepts, motivation, and essential scientific skills such as hypothesis formulation, experiment design, data collection, and analysis. This literature review also reveals a gap in integrating sustainability literacy into inquiry-based experiments. Although some studies have incorporated green chemistry principles and real-world applications, only a few explicitly promote sustainability literacy. This underscores an opportunity for future research to design inquiry-based experiments that more directly address sustainability literacy.